2021
DOI: 10.3390/molecules26134090
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Mitigation via the Foliar Application of Chitosan-Functionalized Selenium and Anatase Titanium Dioxide Nanoparticles in Stevia (Stevia rebaudiana Bertoni)

Abstract: High salt levels are one of the significant and major limiting factors on crop yield and productivity. Out of the available attempts made against high salt levels, engineered nanoparticles (NPs) have been widely employed and considered as effective strategies in this regard. Of these NPs, titanium dioxide nanoparticles (TiO2 NPs) and selenium functionalized using chitosan nanoparticles (Cs–Se NPs) were applied for a quite number of plants, but their potential roles for alleviating the adverse effects of salini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…Significant increase in shoot length was observed at 80 mM concentration which shows the tolerance of selected verity against salinity stress. The maximum surge in fresh weight of shoot was documented at maximum concentration of (80 mM), agrees with study of (Hafez et al, 2021; Sheikhalipour et al, 2021). The minimum concentration, 40 mM was used to achieve the maximum increase in fresh and dry root weight.…”
Section: Discussionsupporting
confidence: 91%
“…Significant increase in shoot length was observed at 80 mM concentration which shows the tolerance of selected verity against salinity stress. The maximum surge in fresh weight of shoot was documented at maximum concentration of (80 mM), agrees with study of (Hafez et al, 2021; Sheikhalipour et al, 2021). The minimum concentration, 40 mM was used to achieve the maximum increase in fresh and dry root weight.…”
Section: Discussionsupporting
confidence: 91%
“…Kumar et al 44 reported that Au-NPs strengthen the antioxidant system in Arabidopsis thaliana while improving the expression of micro-RNAs. Increasing the activities of CAT, SOD, POD, and APX enzymes showed that the line of a defense mechanism by antioxidants was one of the most important mechanisms of Roselle that contributed to the maintenance of its proper, sustainable development, which might explain enhancements in growth parameters 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of studies that confirmed the effect of TiO 2 treatment at a concentration of 0-200 ppm in various crops, in this experiment, the plants were treated with a similar TiO 2 concentration [9,10,12]. TiO 2 foliar spray materials were prepared by mixing 100 mg (T1) or 200 mg (T2) of TiO 2 nanoparticles in 1 L of distilled water containing 1% glycine and stirring for 2 h. TiO 2 solution (T1 or T2) was applied to the foliage at 200 mL per plant on June 26.…”
Section: Tio 2 Treatmentmentioning
confidence: 99%
“…Zahra et al (2017) reported that TiO 2 promotes rice growth, and there is no risk of TiO 2 intake following soil application of TiO 2 [9]. It has been reported that the application of TiO 2 nanoparticles is effective in protecting stevia plants under salt stress conditions by increasing their growth, photosynthetic rate, and antioxidant activity and reducing hydrogen peroxide, malondialdehyde, and electrolytes [10]. In the case of red beans, it is reported that TiO 2 is beneficial for growth by promoting physiological activity [11].…”
Section: Introductionmentioning
confidence: 99%